Influence of flowering time and fruiting pattern on yield components of three cotton genotypes. - Rabadia, V. S.; Thaker, V.S.; Singh, Y.D. (Plant Breeding and Seed Science, 2006)
Cotton genotypes H-6, H-4 (Gossypium hirsutum L.) and V797 (Gossypium herbaceum L.) were analyzed for fruiting pattern (i.e. distribution of flowers, numbers of bolls and its dry weight on different branches) and percent (%) dry matter partitioning into the different components of the boll (seed, fiber and boll wall). Percent distribution of flowers, bolls and dry weight within the plant varied distinctly among the genotypes studied. In higher yielding genotypes (H-4 and H-6), during the initial stage of plant growth for about 10 days, 60-80% of dry matter was partitioned into boll wall and decreased up to 12-15% as the boll developed (nearly 45 days). Contrary to this, seed and fiber accumulated dry matter during development (60-75%). Abscission rate increased with an increase in boll load in all three genotypes and it was significantly higher in the lower yielding variety, V797. A reduction in boll and seed number, seed and fiber dry weight was observed with the progress in the season and was significantly higher in V797 as compared to H-4 and H-6.